Multi-Year Mass-Trapping With Autocidal Gravid Ovitraps has Limited Influence on Insecticide Susceptibility in Aedes aegypti (Diptera: Culicidae) From Puerto Rico. Issue 1 (17th September 2021) - Hemme, Ryan R; Smith, Eric A; Felix, Gilberto; White, Bradley J; Diaz-Garcia, Marta I; Rodriguez, Damaris; Ruiz-Valcarcel, Jose; Acevedo, Veronica; Amador, Manuel; Barrera, Roberto
Abstract: Mass-trapping has been used to control outbreaks of Aedes aegypti (Linnaeus) (Diptera: Culicidae) in Puerto Rico since 2011. We investigated the effect of multi-year, insecticide-free mass trapping had on the insecticide susceptibility profile of Ae. aegypti . Eggs collected in southern Puerto Rico were used to generate F1 populations that were tested for susceptibility to permethrin, sumethrin, bifenthrin, deltamethrin, and malathion according to CDC bottle bioassays protocols. All populations of Ae. aegypti were resistant to the synthetic pyrethroids and mosquitoes from two locations were partially resistant to malathion. Population genetic analysis, using a double digest restriction sites associated DNA sequencing (ddRADseq) approach, indicated a large amount of migration between study sites effectively homogenizing the mosquito populations. Mass-trapping using noninsecticidal autocidal gravid ovitraps did not restore susceptibility to five active ingredients that are found in commercial insecticides. Migration between communities was high and would have brought outside alleles, including resistant alleles to the treatment communities. Further investigation suggests that household use of commercially available insecticide products may continue to select for resistance in absence of public health space spraying of insecticides.